“We are antidepressant also”: aspirin and diclofenac sodium - Sumanth, Meera; Khapale, Prajwala R. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Many studies have indicated that inflammation and depression are associated with each other. Present study was taken up to prove antidepressant effect of aspirin and diclofenac sodium. Methods: The present study was divided into 6 phases with 5 groups of animals N=10. In study 1, C57Bl mice were used and in remaining 4 studies swiss albino mice. Amitriptyline was standard drug used. For each study first group of animals was treated with a saline solution 1ml P.O., and second group of animals injected with 0.1 ml of 2% formalin. In group 3, 4, 5 animals depression was produced by stressors and treated with aspirin 14mg/kg P.O., diclofenac sod. 10 mg/kg P.O. and amitriptyline 10 mg/kg P.O., respectively. Antidepressant activity of aspirin and diclofenac sodium was determined by using forced swim test, tail suspension test, elevated plus maze test and light dark box test. Inflammatory mediators (IL-6, TNF-α) and central neurotransmitters (5-HT, NE, Ach) were estimated. Results: In light dark box test, latency of first crossing, time spent in dark area were decreased and no. of crossing increased significantly in the aspirin, diclofenac sod. treated animals. In forced swim test, the immobility time was decreased. Swiss albino mice treated with aspirin, diclofenac sod. showed decreased concentration of IL-6 and TNF-α and increased concentration of serotonin, nor epinephrine and acetylcholine. In elevated plus maze test, no. of open arm, closed arm entries, time spent in open arm increased and time spent in closed arm decreased. In tail suspension test immobility time was decreased. Conclusions: Aspirin and diclofenac sodium has antidepressant activity.